LEGALITAS PERJANJIAN BAKU ANTARA PT.GRHA CIPTA ARSITAMA MANDIRI DAN KONSUMEN BERKAITAN UNDANG – UNDANG NO.8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Dea Nor Hariani (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT That the legality of a raw deal in Relation to housing law number 8 of 1999 about consumer protection contains many weaknesses, especially for consumer. Is said to have suffered from the lack of agreement by both parties but one party only. While the applicant in providing the deal is fictious. Formally can be said of this standard contract is not valid. However, the Agreement will generally lawfull, if it meets the requirements established law that article 1320 of the civil code which states that terms of his agreement is valid agreement between the parties, ability to make an agreement, a certain thiny and a cause that kosher. Civil code of the terms here so many early forms of agreement that was born who was born without regard to consumer protection act is one of the requirements to make an agreement in the presence of the civil code and the skills many people who approve without paying attention to things that they should get it. This is where a lot of sources of law agreement is legally considered to be feasible of use in an agreement or agreements in everyday life. Thus should be in standard contract must contain an agremment by consumer protection law and article 1320 of the civil code laws. If both articles contained in a agreement then the agreement can be said to be perfect because there is a balance between the rights and obligations of both consumers and developer.Keywords : legality, standart contract, laws number 8 of 1999 about consumer protection